Real-time absorbance monitoring of layer-by-layer coating process of optical fiber pH sensor - Mohd. Yatim, Khairiah (2020)
Fiber optical cable was initially used as waveguides to transmit data over long distances. Various sensor applications can be developed using optical fiber by coating it with different coating materials. Layer-by-layer (LbL) technique is utilized in this research in order to introduce coating layers on sensing region. The utilization of this technique enables the production of scalable ultra-thin film using various materials especially polyelectrolyte. Although various studies had been performed using LbL technique, there still a need to monitor the LbL coating process for optimization of the sensor performance. This is because the performance depends on the coating properties including the thickness of the coat. The main objectives of this research were LbL coating system development, determining the optimal number of bilayers coating on the sensing region and evaluation of fabricated fiber sensor performance. The LbL coating system was developed using power supply, Arduino Uno, stepper motors, breadboard, drivers and laser engraver axis. LbL coating process on optical fiber was monitored in real-time using a white light source and a spectrometer. Multiple layers of poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA) were coated to create pH-sensitive coating on the surface of the optical fiber core. Real-time monitoring of the absorbance spectrum during the coating process was conducted from 0 to 50 PAH/PAA bilayers. Field emission scanning electron microscopy (FESEM) and energy dispersive X-ray spectroscopy (EDX) were used to verify the existence of the fiber coating. The results of EDX proved that the PAH and PAA were coated on the fiber. The monitoring spectrum showed that the absorbance value was increased with the increment of PAH/PAA bilayers up to 30 bilayers and started to decrease as the bilayers exceed that value. The results showed that 30 bilayers of PAH/PAA coatings is the optimum number of bilayers coating for pH sensing due to its high absorbance of 0.87 Optical Density (OD) at 800 nm. The pH sensing performance of fiber without PAH/PAA coating and with 5, 10, 15, 20, 30 and 40 bilayers of PAH/PAA coating were compared by immersing the fiber in pH buffer solutions. The performance was determined through the sensitivity, linearity and repeatability of the sensor. 10 PAH/PAA bilayers coated fiber sensor was 120 times more sensitive than the fiber without coating. This shows that the PAH/PAA coating is highly sensitive to pH as compared with uncoated fiber. The best performance was achieved by 30 bilayers of PAH/PAA coated fiber with a sensitivity of 0.453 OD/pH, linearity of 0.959 and standard deviation value below 4%. Numerous physical, chemical and biological sensors can be produced by utilizing the developed LbL coating system in future.